AMERICA LETTERS AS WITNESSES AND AGENTS OF CHANGE. NORWEGIAN-AMERICAN IMMIGRANT EPISTLES - MUREȘAN, Ioana-Andreea (Studia Universitatis Babeș-Bolyai Philologia, 2021)
America Letters as Witnesses and Agents of Change. Norwegian-American Immigrant Epistles. The letters written by immigrants to their family and friends in the homeland are pieces of a mosaic that provides a wider picture of the personal stories of migration. The analysis of migration has too often focused on statistics, on the mass of people who have emigrated to the New World. However, America letters represent genuine and simple stories of individuals and reflect, in a personal manner, the way immigrants experienced the migration, as well as the way they tried to adapt to a new culture. America letters reveal the enthusiasm, courage and sense of adventure of the immigrants, but also the difficulties, disillusionment, their struggle to belong, even the despair they went through. This paper argues that America letters are witnesses of change, since the immigrants described the challenges of adjustment and acculturation in the letters they sent home, but also agents of change, as they greatly influenced the Norwegian emigration to America. Norway’s coast and valleys were teeming in the nineteenth century with accounts of the conditions in the New World as they were described in the letters sent home by the immigrants. These immigrant letters contain the testimonials of those who had chosen to emigrate and were passed on from family to family, parish to parish, village to village, convincing more and more people to leave the homeland for America. REZUMAT. Scrisorile din America – martori și agenți ai schimbării. Epistole ale imigranților norvegiano-americani. Scrisorile scrise de imigranți către familia și prietenii lor din țara natală sunt piese ale unui mozaic care oferă o imagine mai largă asupra poveștilor personale despre migrație. Analiza migrației s-a concentrat prea des pe statistici, pe masa de oameni care a emigrat în Lumea Nouă. Cu toate acestea, scrisorile din America sunt povești individuale simple și autentice care reflectă, într-o manieră personală, felul în care imigranții au trăit migrația, precum și modul în care au încercat să se adapteze la o nouă cultură. Aceste scrisori dezvăluie entuziasmul, curajul imigranților, simțul aventurii, dar și dificultățile, deziluzia, lupta lor de a-și găsi locul, chiar și disperarea prin care au trecut. Această lucrare arată că scrisorile din America sunt martori ai schimbării, deoarece imigranții au descris dificultățile de adaptare la o nouă cultură în scrisorile trimise acasă, dar și agenți ai schimbării, fiindcă au avut o influență importantă asupra emigrării norvegiene spre America. Coasta și văile Norvegiei abundau în secolul al XIX-lea în relatări despre condițiile din Lumea Nouă, așa cum au fost descrise în scrisorile trimise acasă de imigranți. Aceste scrisori conțin mărturiile celor care au ales să emigreze, mărturii care s-au transmis de la o familie la alta, de la o parohie la alta, de la un sat la altul, convingând tot mai mulți oameni să părăsească Norvegia pentru America. Cuvinte-cheie: emigrarea norvegiană spre America, norvegiano-american, scrisori ale imigranților, scrisori din America, experiența emigrării, evoluția migrației în masă, povești personale despre migrație